School violence: challenges in educating / A violência escolar: desafios no educar - Laudenice Barbosa Bispo; Maria da Conceição Almeida Martins; João Carvalho Duarte (Universidade Estadual de Alagoas, 2019)
The present research the school violence: challenges in the education, is the fruit of a work developed in the Elementary and Middle School Professor Douglas Apratto Tenório, located in the city of Campo Grande-AL This study aimed to promote an interdisciplinary educational policy of prevention and intervention on the problem of violence in our schools, alerting children, adolescents, youth and the local community, educating for peace. In addition, the research reports as specific objectives: work with issues of affectivity, sexuality, drugs and violence, in an interdisciplinary way; to warn adolescents and young people about the causes and consequences of drug use; to address the various types of violence among them: violence against women, physical violence, social violence, psychological violence, sexual violence, school violence. This is a qualitative research where we have evidenced reports of teachers' experiences, of a subjective nature with written and spoken narratives. It is understood that the outcome of this prevention and intervention work has been achieved. This work has alerted our children, adolescents, young people and the whole community about the causes and effects of this disease, which can change their whole life. It contributes to the proposal of continuity of actions, it is necessary to take a careful look at each school year, in order to prevent and intervene in the least sign of violence in the school, look for strategies to face the situation, seek partnerships, as educators and society, we will be assured of our role as transformers for a more just and egalitarian society.